Laboratory manual for clinical anatomy and physiology for veterinary technicians - Colville, Thomas P.; Bassert, Joanna M. (St. Louis, Mo. : Elsevier, 2016)
"Filled with interactive exercises, step-by-step procedure guidelines, and full-color photos and illustrations, this lab manual is designed to help you understand A&P in relation to your clinical responsibilities as a veterinary technician and apply your knowledge in the laboratory setting." --
Anatomic terms -- Microscopy -- Cell anatomy and physiology -- Exploring tissues -- The integumentary system -- The skeletal system -- The muscular system -- The nervous system -- Sense organs -- The endocrine system -- Blood, lymph, and lymph notes -- The cardiovascular system -- The respiratory system -- The digestive system -- The urinary system -- The reproductive system -- Pregnancy, development, and lactation -- Avian anatomy -- Glossary.
"Contributors, Joann Colville, DVM, Jennifer Schurrer, DVM, MS, CCRP."--Contributors, page v.
"Reinforce the A&P principles you've learned in Clinical Anatomy and Physiology for Veterinary Technicians, Third Edition with this practical laboratory resource!" -- Back cover.
Includes index and glossary.
Keywords: Animal Technicians -- Laboratory Manuals; Animals, Domestic -- anatomy & histology -- Laboratory Manuals; Animals, Domestic -- physiology -- Laboratory Manuals; Veterinary anatomy; Veterinary anatomy -- Laboratory manuals; Veterinary dissection; Veterinary dissection -- Laboratory manuals; Veterinary physiology; Veterinary physiology -- Laboratory manuals; Laboratory manuals